Inovasi Pembuatan Kulit Mooncake Dari Tepung Kacang Merah - Saleha Usman; Dhanik Puspita Sari; Tasya Maulidina (Program Studi Hospitality dan Pariwisata, 2022)
The purpose of this study was to obtain a suitable recipe for making mooncake skins made from local food, namely red bean flour and to determine the level of public preference for this innovative product. The research method used is quantitative research, and distributing questionnaires to the panelists in conducting a preference test or organoleptic test on the taste, color, aroma and texture of the product. Processing of data from the results of the questionnaire was processed using descriptive statistics. The results obtained after conducting pre-experiments the authors get the right results for research by providing questionnaires and product samples to expert panelists and consumer panelists, the formulation used is the P2 formulation using 85% red bean flour 15% wheat flour and the P3 formulation using 100% red bean flour. The conclusion of this study is from the 2 formulations obtained and seen from the mean, median, mode, and standard deviation of the results of the organoleptic test questionnaire to expert panelists and consumer panelists, it can be concluded that the preferred formulation is in terms of taste, aroma, color and texture are P3 formulations using 100% red bean flour with an average value of 3.5 for expert panelists and 3.32 for consumer panels